Gamma-aminobutyrate type B receptor modulation of L-type calcium channel current at bipolar cell terminals in the retina of the tiger salamander. - Maguire, G (1989)
Bipolar-cell axon terminals receive direct synaptic input from amacrine-cell processes, suggesting a possible pathway for modulation of transmitter release. In retinal slices, bath-applied baclofen, a gamma-aminobutyrate type B (GABAB) receptor agonist, reduced a patch-clamp-recorded L-type calcium channel current in a population of bipolar cells with axon terminals that ramify along the midline of the inner plexiform layer. Lucifer yellow staining revealed that this current was found only in bipolar cells that retain axon terminals and their associated telodendria, suggesting that the current is generated at the terminal and also possibly modulated there. T-type calcium currents were found in all bipolar cells, including those without axon terminals, but were not modulated by baclofen. The baclofen-induced reduction of calcium current was enhanced by guanosine 5'-[gamma-thio]triphosphate and eliminated by guanosine 5'-[beta-thio]diphosphate added to the cytoplasm by the patch recording electrode, suggesting that the GABAB receptors act through a guanine nucleotide-binding regulatory protein (G protein). Baclofen also reduced an excitatory synaptic input to a population of amacrine cells with processes that ramify along the midline of the inner plexiform layer--cells probably postsynaptic to the bipolar terminals. This suggests that GABAB receptors modulate not only the calcium current but also transmitter release by a pathway involving G proteins and L-type calcium channels.